2015
DOI: 10.1002/2014jb011595
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional dynamic rupture simulations across interacting faults: TheMw7.0, 2010, Haiti earthquake

Abstract: The mechanisms controlling rupture propagation between fault segments during a large earthquake are key to the hazard posed by fault systems. Rupture initiation on a smaller fault sometimes transfers to a larger fault, resulting in a significant event (e.g., 2002 M7.9 Denali USA and 2010 M7.1 Darfield New Zealand earthquakes). In other cases rupture is constrained to the initial fault and does not transfer to nearby faults, resulting in events of more moderate magnitude. This was the case of the 1989 M6.9 Loma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Bimaterial fault interfaces also influence ground motion during an earthquake [Ben-Zion, 2001]. Therefore, this result is vital to assess ground motion level from potential earthquake scenarios mainly on the EPGF not only because this fault still remains a major seismic threat for the nearby cities in southern Haiti [Calais et al, 2010;Douilly et al, 2015;Prentice et al, 2010;Symithe et al, 2013] but also because sedimentary basin could trap the energy and significantly amplify the ground shaking [Day et al, 2006;Olsen, 2000;Wald and Graves, 1998]. As an example, Komatitsch et al [2004] used a spectral element method to simulate ground motion in the Los Angeles basin and their results uncover large amplification within the basin for their 3-D simulation with respect to their 1-D case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bimaterial fault interfaces also influence ground motion during an earthquake [Ben-Zion, 2001]. Therefore, this result is vital to assess ground motion level from potential earthquake scenarios mainly on the EPGF not only because this fault still remains a major seismic threat for the nearby cities in southern Haiti [Calais et al, 2010;Douilly et al, 2015;Prentice et al, 2010;Symithe et al, 2013] but also because sedimentary basin could trap the energy and significantly amplify the ground shaking [Day et al, 2006;Olsen, 2000;Wald and Graves, 1998]. As an example, Komatitsch et al [2004] used a spectral element method to simulate ground motion in the Los Angeles basin and their results uncover large amplification within the basin for their 3-D simulation with respect to their 1-D case.…”
Section: Discussionmentioning
confidence: 99%
“…They also infer that a change in elastic properties with depth could explain the upward termination of the Loma Prieta earthquake. The 2010 Haiti earthquake and the 1989 Loma Prieta earthquake share several similarities in tectonics and earthquake rupture processes [Douilly et al, , 2015Symithe et al, 2013]. They both involved rupture initiation on smaller blind thrust fault adjacent to major strike-slip fault without transferring to the main fault.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, numerical simulations incorporating the mechanics of earthquake rupture (hereafter termed dynamic simulation) revealed that the earthquake rupture, under typical tectonic loading, is controlled by intrinsic features of the fault macroscopic structure . In particular, the fault geometry plays a significant role in the earthquake process as inferred from numerical simulations (e.g., Harris and Day, 1999;Oglesby et al, 2003;Aochi and Kato, 2010;Kase, 2010;Fukuyama and Hao, 2013;Douilly et al, 2015), as well as from geological observations (e.g., King and Nábĕlek, 1985;Wesnousky, 2008). The aim of this study is to make use of high-performance computing of dynamic simulations to infer the likelihood of several earthquake scenarios in the Sea of Marmara.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of earthquake rupture in complex scenarios or involving earthquake sequences often use the so-called quasi-dynamic approach (Erickson & Day, 2016;Erickson & Dunham, 2014;Douilly et al, 2015;Rice, 1993;Rice et al, 2001;Wei et al, 2013), in which inertial effects are neglected. Slip instability under quasi-static mechanics leads to unbounded slip speeds, and the singularity is resolved through a radiation damping approximation, that is, by adding a velocity-dependent cohesion that bounds the slip velocity at rupture fronts (Rice, 1993;Rice et al, 2001).…”
Section: Introductionmentioning
confidence: 99%